The Development of Wireless Power Transfer Technologies for Mobile Charging in Vehicles using Inductive Approach - Gnanasegaran, S.; Saat, S.; Rahman, F.K.A.; Husin, S.H.; Khafe, A.; Isira, A. S. M.; Darsono, A. M.; Yahya, A.; Yusop, Y.; Shaari, N.M.M. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Nowadays, the mobile charging in vehicle is a must and therefore, such technology is now available in every vehicle through wired connection approach. Using this wired connection to power up mobile device in the vehicle might be inconvenience to the user. Thus, this project aims to develop a wireless power transfer technology to power up the mobile device in a vehicle. Through this, the users will not facing difficulty of charging their device while driving. To be specific, the Inductive Power Transfer (IPT) is applied here due to its advantages where it can transfer power wirelessly with a higher efficiency in a short range. To make this work, a Class E inverter is designed to convert a direct current (DC) supply into alternating current (AC) supply at a high frequency with a higher efficiency. Furthermore, pi-2-a impedance matching circuit is also applied in this work in order to improve the efficiency of such system. To validate the efficiency of the proposed method, analysis on the gap distance between the two magnetic coils, transmitter and receiver, are performed through simulation and experimental work. At the end of this work, the designed prototype is able to yield approximately 70 % in terms of output efficiency and able to power up the mobile device wirelessly.